2004
DOI: 10.1002/cne.20323
|View full text |Cite
|
Sign up to set email alerts
|

Expression of dopamine and vesicular monoamine transporters and differential vulnerability of mesostriatal dopaminergic neurons

Abstract: Numerous studies suggest that the dopamine transporter (DAT), responsible for dopamine reuptake, may act as a vulnerability factor in the pathogenesis of Parkinson's disease (PD) and the vesicular monoamine transporter (VMAT2), responsible for its vesicular storage, as a neuroprotective factor. However, the relevance of each on the differential vulnerability of midbrain DA cells remains unknown. Here we studied the relationship between the expression pattern (mRNA and protein) of both transporters and the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 86 publications
7
53
0
1
Order By: Relevance
“…It is well known that A9 dopamine neurons are more vulnerable to toxic insults than A10 neurons (Barroso-Chinea et al 2005;Gibb 1992;Gonzalo-Hernandez et al 2004;Kish et al 1988). It cannot be determined from this study whether TNFα treatment affected specifically A9 or A10 dopamine neurons.…”
Section: Discussionmentioning
confidence: 75%
“…It is well known that A9 dopamine neurons are more vulnerable to toxic insults than A10 neurons (Barroso-Chinea et al 2005;Gibb 1992;Gonzalo-Hernandez et al 2004;Kish et al 1988). It cannot be determined from this study whether TNFα treatment affected specifically A9 or A10 dopamine neurons.…”
Section: Discussionmentioning
confidence: 75%
“…It is widely elucidate that 6-OHDA is taken up by dopaminergic neurons via DAT (Tranzer and Thoenen 1973) and auto-oxidation process occurs intracellularly (Glinka et al 1997) manly because the toxicity can be blocked by DAT inhibition (González-Hernández et al 2004). On the other hand, previous data have shown that 6-OHDA uptake is not an essential process and the autooxidation occurs extracellularly in undifferentiated cells (Izumi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These neurons are at particular risk in PD, whereas DA neurons in ventral tegmental area (or A10) are predominantly calbindin ϩ (Gerfen et al, 1987). In both rodent and primate adult midbrain, the levels of DAT mRNA (Sanghera et al, 1994;Haber et al, 1995) and DAT protein (Gonzalez-Hernandez et al, 2004) are higher in calbindin Ϫ than in calbindin ϩ DA neurons. In vivo studies both in rodents and primates show that the neurons of the rostromedial region of substantia nigra, the majority of which are calbindin ϩ , express higher level of VMAT2 than the caudoventral regions of substantia nigra, the majority of which are calbindin Ϫ (GonzalezHernandez et al, 2004).…”
Section: Discussionmentioning
confidence: 99%